Pengaruh Pengetahuan Dan Pemasaran Terhadap Minat Nasabah Pada Produk Gadai Emas - Moh Khoirul Anam; Nadia Kulsum (LPPM ISNJ Bengkalis, 2022)
Pawn gold is the flagship product of Islamic banks, and this product has low risk, is profitable, and has the potential to increase bank assets. This study aimed to show the effect of knowledge and marketing on customer interest in gold pawn products at Bank Jabar Banten Syariah (BJBS) sub-branch office Bumi Serpong Damai, South Tangerang. This research uses quantitative methods using multiple linear regression analysis using SPSS Version 23. The population of this study is customers of BJBS sub-branch office Bumi Serpong Damai who are users of savings products totaling 1,276 people. Measurement of the sample using the Slovin method obtained a total sample of 93 customers. Data was collected by distributing questionnaires to respondents using the incidental method. The results showed that knowledge did not affect customer interest. Marketing has a positive and significant effect on customer interest. Simultaneously, knowledge and marketing significantly affect customer interest, amounting to 69.5%. This research can complement existing theories and be a reference for Islamic banking in gaining customer interest in gold pawn products.